ISU-ISU PENDIDIKAN PENDIDIKAN AGAMA ISLAM (PAI) DI INDONESIA - Sukari; Hanik Rahmawati Solikhah; Anny Izzatul Mujahidah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Islamic Religious Education (PAI) holds a strategic position in Indonesia's national education system, particularly in shaping the character, morals, and spirituality of students. However, the implementation of PAI education in Indonesia still faces various complex challenges, ranging from curriculum aspects, teacher competency, learning methodology, to the challenges of globalization and religious moderation. This article aims to comprehensively examine issues in PAI education in Indonesia using a literature review approach from scientific journals and academic books. The method used is a literature review of journal articles and primary reference books relevant to Islamic education. The results of the study indicate that the main problems in PAI education lie in the curriculum that is not fully contextual, learning methods that are still conventional, limited competency of PAI teachers, and the weak integration of religious moderation values ​​and digital literacy. This article is expected to serve as an academic reference for the development of PAI education policies and practices that are more relevant to the needs of the times.